PELAKSANAAN PROGRAM SISTEM INOVASI DAERAH PELAYANAN SATU HARI SIAP (SHS) OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN ROKAN HULU TAHUN 2014-2015 - Wicaksono, Baskoro; As’ari, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The birth certificate is a document that should be owned by every citizen of Indonesia. Rokan Hulu in this case the Department of Population and Civil Registration makes one form of service innovation that initially this birth certificate service takes 14 business days, converted into a day's work, called the program One Day Ready (SHS). SHS services were made because the civil registration of birth certificates in the field of Rokan Hulu is still relatively low. The purpose of this program was launched to improve the recording field of a birth certificate. The problems of this research are how the implementation of the program service of One Day Ready (SHS) on the quality of public services. This study aims to investigate the implementation of the service program One Day Ready (SHS) on the quality of public services by the Department of Population and Civil Registration Rokan Hulu years 2014-2015. This research uses descriptive qualitative method. Sources of data in this study of informants and review documents related to this program are One Day Ready (SHS). The Data collection technique with in-depth interviews (in-depth interviews), documentation and direct observation. Data analysis technique with data reduction, data presentation, inference and verification. From the results of this research is that the implementation of the program One Day Ready (SHS) in the service of the birth certificate presented by the Department of Population and Civil Registration Rokan Hulu is good. Judging from some of the important aspects in the implementation of a program that Communication, Resources, Disposition, and Bureaucratic Structure. All the important aspects have achieved good based on research that has been done. Keywords: Public Services, Program, Regional Innovation.